Effect of Fresh and Fermented Olive Solid Waste in content of total phenols in Calcareous Soil and Wheat Plant Productivity (Journal of Hama University, 2020)
A field experiment was conducted at the Faculty of Agriculture farm in Abu Jarash, using different rates of fresh and fermented olive solid waste according to the following: (control + mineral fertilizer NPK, fresh olive solid waste 100%, fresh olive solid waste 75%+ cow manure25%,  fresh olive solid waste 50%+ cow manure50%, fermented olive solid waste 100%, fermented olive solid waste 75%+ cow manure25%, fermented olive solid waste 50%+ cow manure50%(. Mineral fertilizer and olive solid waste were added according to nitrogen utilization coefficient and Wheat cultivationThe total phenols were extracted and estimated in all treatments after harvest. Fresh olive solid waste 100% treatment showed that there were significant differences compared fermented olive soled waste 100% which its value was 490.2 mg/kg-1, while fermented olive soled waste100% showed less of total phenols content which its value was 266.5 mg/kg-1 . The treatments order according to their content of total phenols as following: (fresh olive solid waste 75%+ cow manure25%, fresh olive solid waste 50%+ cow manure50%, fermented olive solid waste 75%+ cow manure25%, fermented olive solid waste 50%+ cow manure50%, Mineral fertilizer and finally the control treatment (the values in each treatments were (462.6, 398.3, 266.5, 248.2, 239.0, 214.5 and 176.2) mg/kg-1 in the same previous order. The best productivity was in fermented olive solid waste100% treatment (5.980) tons.h-1 and the lowest value in the control treatment (3.987) tons.h-1